IMPLEMENTASI MEDIA MAGIC STAIRS 3 DIMENSI PADA MATERI SATUAN PANJANG TERHADAP HASIL BELAJAR SISWA KELAS 3 DI UPPT SDN 02 TANJUNGSARI KOTA BLITAR - Khusnia, Lia; Shofi Nur Amalia; Ragil Tri Oktaviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Students' low understanding can result in learning outcomes that are not maximized in learning, therefore the purpose of this study is to implement 3-Dimensional Magic Stair media on student learning outcomes. This research includes Classroom Action Research (PTK) which consists of 4 stages, namely the planning stage, the implementation stage, the observation stage, and also the reflection stage. Researchers conducted research with II cycle steps and each cycle consisted of 2 meetings. Researchers used several data collection techniques, including: observation, interviews, tests and documentation. This research was conducted in class 3 UPT SDN 02 Tanjungsari Blitar City. The result of this study is a significant increase in student learning outcomes in math unit length. In addition to the increase in learning evaluation results, there was a percentage of students who touched the KKM score from 58.3% in pre-action to 70.8% in cycle I and ended in cycle II with a percentage of 87.5%.